Analisis Wacana Kritis Vidio Penanggulangan Covid-19 Pemerintah Jawa Timur Di Facebook - Maulidatus Syahrotin Naqqiyah; Ellyda Retpitasari (Connected: Jurnal Ilmu Komunikasi, 2020)
This Study discusses the news text of government communication planning news related to the Covid-19 pandemic uploaded by East Java Provincial Government in one of its social media accounts,Facebook. This study uses qualitative researc methods by using documents as the main research data. In additio, this discourse text analysis research also uses Teun Van Dijk discours analysis model with research result that are schematically, the text in the information uploaded in the Eas Java provincial Facebook account can be clearly an easily understood by people from various circles with information that is up to date and rhetorically the information is updated by emphasizing the existence of photos or pictures as evidence of the actions of the east java provincial government programs.